Harmonization of Open Banking Regulations and Personal Data Protection: A Comparative Analysis of Indonesia, Japan, and the European Union - Amaliyah Amaliyah; Trisadini Prasastinah Usanti; Yuniarti Yuniarti; Geofani Milthree Saragih; Muhammad Tizar Adhiyatma (Jurnal Pembaharuan Hukum, 2026)
The rapid advancement of financial technology has led to the emergence of open banking systems, which grant standardized access to consumers’ financial data for third parties. This transformation presents significant opportunities for innovation while also raising serious challenges to personal data protection. This study aims to analyze the regulatory frameworks of open banking and personal data protection in Indonesia, Japan, and the European Union using a normative juridical method and comparative legal approach. The analysis examines policy structures, legal instruments, and supervisory mechanisms within each jurisdiction. The findings reveal that the European Union provides the most comprehensive legal framework through the integration of PSD2 and GDPR, ensuring a balance between financial innovation and privacy protection. Japan adopts a regulatory model emphasizing technical security and third-party licensing but still faces challenges in harmonizing with international standards. Indonesia remains in an early stage, with fragmented regulations between the banking and personal data protection sectors, necessitating regulatory synchronization to ensure legal certainty and consumer protection. This article recommends cross-sector harmonization and stronger regulatory oversight to build a secure and inclusive open banking ecosystem.